Ethylene Role in Plant Growth, Development and Senescence: Interaction with Other Phytohormones - Iqbal, Noushina; Khan, Nafees A.; Ferrante, Antonio; Trivellini, Alice; Francini, Alessandra; Khan, M. I. R. (Frontiers in Plant Science, 2017)
The complex juvenile/maturity transition during a plant’s life cycle includes growth, reproduction, and senescence of its fundamental organs: leaves, flowers, and fruits. Growth and senescence of leaves, flowers, and fruits involve several genetic networks where the phytohormone ethylene plays a key role, together with other hormones, integrating different signals and allowing the onset of conditions favorable for stage progression, reproductive success and organ longevity. Changes in ethylene level, its perception, and the hormonal crosstalk directly or indirectly regulate the lifespan of plants. The present review focused on ethylene’s role in the development and senescence processes in leaves, flowers and fruits, paying special attention to the complex networks of ethylene crosstalk with other hormones. Moreover, aspects with limited information have been highlighted for future research, extending our understanding on the importance of ethylene during growth and senescence and boosting future research with the aim to improve the qualitative and quantitative traits of crops.